HORIZON HARAPAN PADA NOVEL WISANGGENI: SEBUAH TINJAUAN AWAL RESEPSI SASTRA - Jaki Yudin (STKIP PGRI SUMENEP, 2023)
Every literary work is enjoyed by readers with a background of knowledge and experience that generates a response. This study aims to describe the reader's response to the novel. The source of data in this research is the text of a novel entitled